Effects of water and nitrogen coupling on the plant growth and quality of greenhouse tomatoes at the first flowering and fruiting stages - Chen, Danyan; Li, Hailing; Wang, Xinyi; Ma, Jingze; Li, Shilong; Jiang, Xiaorui; Dai, Aijun; Yu, Hao; Zhang, Yingying; Liu, Ya (International Journal of Agricultural and Biological Engineering, 2025)
Good growth of tomato at the early growing stages is the key to final yield formation, for which water (W) and nitrogen (N) applications are two necessary factors. In this study, two irrigating systems (W1, W2) and three N applications (N1, N2, N3) were interacted (W×N) to plant the cherry tomato variety ‘‘Jinling Meiyu’’ in greenhouse. W1 (reduced irrigation) and W2 (normal irrigation) had a 7:9 irrigated ratio based on former research. N1, N2, and N3 were set at 100%, 80%, and 60% normal N application, respectively. The tomato plant height (PH), stem circumference (SC), number of leaves (NL), number of first order fruits (NF), the single fruit weight (SFW), contents of fruit Vitamin C (VC) and soluble sugar (SS), fresh weights of root (RW), leaf (LW), and plant stem (PSW), as well as leaf chlorophyll fluorescence value (SPAD), temperature (T), humidity (RH), and nitrogen content (N) were investigated at the first flowering and fruiting stage. The results showed that W×N had significant impacts on early plant growth and fruit quality of tomato. W2N2 obviously received the largest values of tomato PH (152.5 cm), SC (4.1 cm), NF (11 fruits/plant), and LW (45.0 g/plant), but obtained the lowest VC (9.71 mg/kg) and SS (2.40%). However, W1N3 had the largest values of leaf RH (56.9%), N contents (14.23 mg/g), and VC (16.29 mg/kg), with NF also at 11.0 fruits/plant. W2N1 significantly had the highest RW (14.4 g/plant), PSW (71.8 g/plant), and SFW (21.3 g/fruit). W2N3, W1N1, and W1N2 obtained the most NL (103.7 pieces/plant), SS (4.06%), and leaf SPAD (36.85), respectively. Pearson correlation analysis results showed PH negatively significantly correlated with NF (p<0.05). The leaf SPAD positively significantly correlated with PH (p<0.05) and RH (p<0.01), but negatively significantly correlated with SC (p<0.05) and T (p<0.01). Moreover, leaf N content also had a positive significant correlation with PH (p<0.05), and an extremely positive significant correlation with RH and SPAD (p<0.01). However, it negatively significantly correlated with SC (p<0.01) and T (p<0.05). Significantly, VC had positive correlations with PSW, leaf SPAD, and N content (p<0.05). SS negatively correlated with PSW (p<0.05) and T (p<0.01), and extremely significantly positively correlated with SPAD (p<0.01). Additionally, RW had an extremely significant relationship with PSW (p<0.01). Two-factor analysis of variances showed W extremely significantly influenced leaf T, RH, SPAD, and N content (p<0.001), as well as SC (p<0.01) and SS (p<0.05). Meanwhile, N management extremely significantly influenced LW (p<0.001), RW (p<0.01), and leaf T (p<0.05). However, W×N obviously significantly influenced just PSW (p<0.01), RW (p<0.001), and VC (p<0.05). Taking all factors into account, the early reasonable W×N management could promote growth of tomato plants and fruit quality at the first fruiting and ripening stage. These results could provide a foundation for the subsequent growth of tomato fruits and could also be beneficial for the precise management of greenhouse tomatoes at the early growing stages. Keywords: greenhouse tomato, water and nitrogen interaction, leaf growth, SPAD value, nitrogenDOI: 10.25165/j.ijabe.2024180x.8781Citation: Chen D Y, Li H L, Wang X Y, Ma J Z, Li S L, Jiang X R, et al. Effects of water and nitrogen coupling on the plant growth and quality of greenhouse tomatoes at the first flowering and fruiting stages. Int J Agric & Biol Eng, 2025; 18(1): 181–190.